2009
DOI: 10.24039/rnh2009321119
|View full text |Cite
|
Sign up to set email alerts
|

Lesiones Patológicas Causadas Por Profilicollis Altmani (Perry, 1942) Van Cleave, 1947 (Acanthocephala) en Una Gaviota Gris (Leucophaeus Modestus) (Tschudi, 1843) De La Costa Peruana

Abstract: Las lesiones patológicas causadas por acantocéfalos en aves marinas son poco conocidas. En este sentido, se presenta un estudio de las lesiones patológicas en una gaviota gris (Leucophaeus modestus) (Tschudi, 1843) por el acantocéfalo Profilicollis altmani (Perry, 1942) Van Cleave, 1947. Macroscópicamente, se encontró un engrosamiento de la pared intestinal circunscrito a la profunda área de penetración de los gusanos, con nódulos blanquecinos en la serosa. Microscópicamente, se observó la penetración del extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The histopathology results are similar to others described by Amin et al [ 13 ] of Moniliformis saudi Amin, Heckmann, Mohammed, Evans, 2016 (Moniliformidae) in Paraechinus aethiopicus (Ehrenberg) [ 13 ] from Saudi Arabia and of Centrorhynchus globirostris Amin, Heckmann, Wilson, Keele, Khan, 2015 (Centrorhynchidae) in Centropus sinensis (Stephens) from Pakistan [ 39 ] as well as those of Pomphorhynchus kashmirensis Kaw, 1941 (Pomphorhynchidae) in Schizothorax plagiostomus Heckel [ 12 ] from Kashmir. Gonzales-Viera et al [ 32 ] provided the only other histopathological study of P. altmani in another definitive host species, the gray gull, Leucophaeus modestus (Tschudi) from the Peruvian coast. Their sections were different from ours focusing on the attachment sites featuring proboscis invasion of the villi with adjacent central necrosis, inflammatory infiltrates, hyperplasia, granuloma in the submucosa, and peripheral dense fibrous and vascularized connective tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The histopathology results are similar to others described by Amin et al [ 13 ] of Moniliformis saudi Amin, Heckmann, Mohammed, Evans, 2016 (Moniliformidae) in Paraechinus aethiopicus (Ehrenberg) [ 13 ] from Saudi Arabia and of Centrorhynchus globirostris Amin, Heckmann, Wilson, Keele, Khan, 2015 (Centrorhynchidae) in Centropus sinensis (Stephens) from Pakistan [ 39 ] as well as those of Pomphorhynchus kashmirensis Kaw, 1941 (Pomphorhynchidae) in Schizothorax plagiostomus Heckel [ 12 ] from Kashmir. Gonzales-Viera et al [ 32 ] provided the only other histopathological study of P. altmani in another definitive host species, the gray gull, Leucophaeus modestus (Tschudi) from the Peruvian coast. Their sections were different from ours focusing on the attachment sites featuring proboscis invasion of the villi with adjacent central necrosis, inflammatory infiltrates, hyperplasia, granuloma in the submucosa, and peripheral dense fibrous and vascularized connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Their sections were different from ours focusing on the attachment sites featuring proboscis invasion of the villi with adjacent central necrosis, inflammatory infiltrates, hyperplasia, granuloma in the submucosa, and peripheral dense fibrous and vascularized connective tissue. Gonzales-Viera ([ 32 ], page 115) further concluded that P. altmani “causes severe eosinophilic granulomatous enteritis in the gray gull.”…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation